Developing and validating a comprehensive measure of coordination in patient aligned care teams - Amber B. Amspoker; Houston F. Lester; Christiane Spitzmueller; Candice L. Thomas; Sylvia J. Hysong (BMC, 2022)
Abstract Background/Objective Despite numerous extant measures assessing context-specific elements of care coordination, we are unaware of any comprehensive, team-based instrument that measures the requisite mechanisms and conditions required to coordinate successfully. In this study we develop and validate the psychometric properties of the Coordination Practices Survey, a context-agnostic measure of coordination for primary care teams. Methods Coordination items were developed based on a systematic literature review; items from previously developed scales were adapted and new items were created as needed; all items were refined after subject matter expert review and feedback. We collected data from Primary Care teams drawn from 1200 Veterans Health Administration (VHA) medical centers and outpatient clinics nationwide. 1645 primary care team members from 512 patient aligned care teams in the Veterans Health Administration completed the survey from 2015 to 2016. Psychometric properties were assessed after data collection using Cronbach's alpha, intraclass correlations and multilevel confirmatory factor analysis to assess the factor structure. Results Our findings confirmed the psychometric properties of two distinguishable subscales of coordination: (a) Accountability and (b) Common Understanding. The within- and between-team latent structure of each subscale exhibited adequate fit to the data, as well as appropriately high Cronbach's alpha and intraclass correlations. There was insufficient variability in responses to the predictability subscale to properly assess its psychometric properties. Conclusion With context-specific validation, our subscales of accountability and common understanding may be used to assess coordination processes in other contexts for both research and operational applications.